Small extracellular vesicles deliver miR-21 and miR-217 as pro-senescence effectors to endothelial cells. Issue 1 (1st January 2020) - Mensà, Emanuela; Guescini, Michele; Giuliani, Angelica; Bacalini, Maria Giulia; Ramini, Deborah; Corleone, Giacomo; Ferracin, Manuela; Fulgenzi, Gianluca; Graciotti, Laura; Prattichizzo, Francesco; Sorci, Leonardo; Battistelli, Michela; et al.
ABSTRACT: The role of epigenetics in endothelial cell senescence is a cutting-edge topic in ageing research. However, little is known of the relative contribution to pro-senescence signal propagation provided by microRNAs shuttled by extracellular vesicles (EVs) released from senescent cells. Analysis of microRNA and DNA methylation profiles in non-senescent (control) and senescent (SEN) human umbilical vein endothelial cells (HUVECs), and microRNA profiling of their cognate small EVs (sEVs) and large EVs demonstrated that SEN cells released a significantly greater sEV number than control cells. sEVs were enriched in miR-21-5p and miR-217, which target DNMT1 and SIRT1. Treatment of control cells with SEN sEVs induced a miR-21/miR-217-related impairment of DNMT1-SIRT1 expression, the reduction of proliferation markers, the acquisition of a senescent phenotype and a partial demethylation of the locus encoding for miR-21. MicroRNA profiling of sEVs from plasma of healthy subjects aged 40–100 years showed an inverse U-shaped age-related trend for miR-21-5p, consistent with senescence-associated biomarker profiles. Our findings suggest that miR-21-5p/miR-217 carried by SEN sEVs spread pro-senescence signals, affecting DNA methylation and cell replication.